Implementasi Program Pemberdayaan UMKM Berbasis Legalitas Usaha di Kabupaten Pulang Pisau - Andre Januarta; Muhammad Irvan Yazid Azhar Pasaribu (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
The MSME empowerment program in Pulang Pisau Regency places business legality as the primary foundation in the development and distribution of government assistance. Legality such as Business Identification Numbers (NIB) and micro-business permits are used to ensure the accuracy of targeting and validity of business actor data. This study aims to analyze the implementation of the MSME empowerment program based on business legality using a descriptive qualitative approach and referring to Edward III's Policy Implementation Theory, which emphasizes four main variables: policy communication, resources, implementer disposition, and bureaucratic structure. Data were obtained through in-depth interviews with local government officials and MSME actors, as well as analysis of related policy documents. The results show that business legality has been consistently implemented as an administrative requirement and program evaluation indicator, reflecting a fairly clear bureaucratic structure and relatively focused policy communication. However, MSME actors still face obstacles in terms of resources and implementation support, particularly related to marketing, logistics costs, and the lack of supporting infrastructure such as MSME product centers. In addition, implementer dispositions have supported the program, but have not fully met MSME needs for market access and further assistance. These findings indicate that legality-based implementation has been successful administratively, but further strengthening of resources and structural support is needed to ensure optimal and sustainable MSME empowerment programs.